Using Python programming to foster students’ scientific thinking - Nadezhda Gallini; Anatoliy Kazak; Nataliya Gorbunova; Victor Gallini; Anisa Atik; Elena Sergeeva (Institute of Advanced Engineering and Science, 2026)
This paper explores the role of programming not only as a technical skill but also as a method for developing students’ scientific thinking. The study is based on an experiment involving 258 university students who completed a course designed to foster logical, analytical, and project-based cognitive strategies. The experiment was conducted at V.I. Vernadsky Crimean Federal University, Humanities and Education Science Branch, Yalta, Russia. The proposed model integrates elements of the technological pedagogical content knowledge (TPACK) framework with a custom-designed pedagogical approach, treating programming as a universal structure for processing and representing information. The data suggest that systematic engagement with programming enhances students’ ability to solve complex problems, conceptualize, decompose tasks, and apply reflective design. The findings emphasize the need to rethink the role of programming in higher education curricula across disciplines, beyond purely technical training.